Nudging for online misinformation: a design Inquiry - Konstantinou, Loukas; Karapanos, Evangelos (My University, 2023)
The use of technology to combat online misinformation is becoming a prominent topic of research and practice, yet most of the existing solutions do not consider the impact of cognitive biases in misinformation-related decision-making. Addressing this gap, the present paper explores the potential of nudging to inform the design of technological interventions that combat misinformation. We report on a design workshop with 29 participants, who were asked to conceive technology-mediated nudges for misinformation with the use of the "Nudge Deck", a design-support tool that presents 23 interaction design mechanisms for nudging
Keywords: Nudging; Online misinformation; Design workshop; Behavior change